2021
DOI: 10.26633/rpsp.2021.12
|View full text |Cite
|
Sign up to set email alerts
|

HIV among men who have sex with men in the Caribbean: reaching the left behind

Abstract: Objectives. To present the epidemiology, social and cultural factors driving the HIV epidemic among men who have sex with men (MSM) in the Caribbean region and to highlight the regional and national responses, and what remains to be addressed to close the gaps in order to ending AIDS by 2030. Methods. A literature review was performed in the following databases: PubMed and Scopus. Articles published in the past 10 years were selected. The outcomes of interest were sociocultural risk factors, description of reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…33 These experiences may discourage longer-term relationships, and encourage anonymous and condomless sex, as well as avoidance of health services. 1,4,30 Over 50% of MSM in Jamaica report having sex with females. 1,30 HIV stigma and homophobia intersect in Jamaica, which may be driving the HIV epidemic among MSM and undermining uptake of HIV prevention and support services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 These experiences may discourage longer-term relationships, and encourage anonymous and condomless sex, as well as avoidance of health services. 1,4,30 Over 50% of MSM in Jamaica report having sex with females. 1,30 HIV stigma and homophobia intersect in Jamaica, which may be driving the HIV epidemic among MSM and undermining uptake of HIV prevention and support services.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,30 Over 50% of MSM in Jamaica report having sex with females. 1,30 HIV stigma and homophobia intersect in Jamaica, which may be driving the HIV epidemic among MSM and undermining uptake of HIV prevention and support services. 32 Studies elsewhere have shown that provider stigma and discrimination including heterosexism can undermine access to PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…One frequently cited contextual HIV risk factor in the Caribbean is anti-gay prejudice (Beck et al , 2017; Dunbar et al , 2021). Research suggests that MSM who experience homophobia are more likely to engage in risk behaviours associated with HIV transmission (Takada et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…En este país, en Salvador de Bahía, el 57,7% habían experimentado algún tipo de discriminación y el 43,5% informaron no haberle dicho a sus padres, sobre su atracción sexual por otros hombres 26 . Existe mayor discriminación en los HSH jóvenes 27 , como se presentó en Brasil (menores de 30 años), que han estudiado por más de ocho años, con poca participación y apoyo de la comunidad, presencia de violencia física y sexual, ideación suicida en los últimos seis meses 25 , evitar servicios de prevención ante el VIH 28 .…”
Section: Introductionunclassified